Tracing spectres of whiteness: discourse and the construction of teaching subjects in urban Aboriginal education. Issue 5 (3rd September 2017) - Madden, Brooke
ABSTRACT: The author traces how discourse functions in the context of a school-based, urban Aboriginal education initiative, with a focus on the construction and organization of teaching subjects. Critical discourse analysis that traces spectres reveals some of the ways that whiteness and Eurocentrism create the possibilities for, and the conditions in which teachers take up, the positions: victim of racism, arbiter of authenticity, and rescuer. Consideration of the multiple, complex, and shifting positions teachers occupy within whiteness in general, and in colonial systems of education in particular, offers unique possibilities when untangling and reconfiguring teachers' constructions of Aboriginality/Indigeneity and responses to Aboriginal/Indigenous education. This theory building also contributes to the larger field of curriculum studies by demonstrating how consideration of 'unheroic tales' can aid in theorizing teacher identity and difference, both within and beyond the markers Indigenous/non-Indigenous.